Desain Prototipe Handwell Universal Tool Grinding Machine Menggunakan Konsep Manufaktur Teknologi 3D Printer - Roberth Marshall Ratlalan (Politeknik Negeri Ujung Pandang, 2022)
Abstract : The presence of the manufacturing world has brought a huge impact on the progress of science and technology in the industry which is currently growing rapidly, especially in the field of industrial automation. Additive Manufacturing known as 3D printing Technology in its philosophy of helping humans in completing every task by playing a very important role in product development, prototyping, and manufacturing process.The results of the manufacturing process using a 3D printer are very good, where the design results can be translated to a 3D Printer and produce objects that match the design results from the software inventor. Success in this manufacturing process is obtained from the results of setting the 3D printer parameters during the proper slicing process, such as setting material temperature, support, printer speed, fan speed, layer thickness (quality), wall thickness (Shell), Infill (filler). and others. Keywords: Prototype Design, 3D Printer, Manufacturing Process